2022
DOI: 10.1111/zph.12939
|View full text |Cite
|
Sign up to set email alerts
|

A national study through a ‘Farm‐to‐fork’ Approach to determine Salmonella dissemination along with the Lebanese poultry production chain

Abstract: This cross‐sectional study was conducted to determine the prevalence of Salmonella at different stages of the broiler production chain and layer flocks in addition to their antibiotic resistance profile and molecular patterns. Over a period of 3 years, different sample matrices were collected from Lebanese farms, slaughterhouses and retail markets. Out of 672 Salmonella serotyped, 514 were analysed for antimicrobial resistance and 214 for clonality using Pulsed‐field gel electrophoresis (PFGE). The results hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 43 publications
1
9
0
Order By: Relevance
“…in live chickens at the time of slaughtering differs across countries. A recent study in Egypt ( Elsayed et al, 2024 ) revealed rates comparable to those in Jordan, with a range of 12 to 17%, while a study in Lebanon ( El Hage et al, 2022 ) revealed rates as high as 31.4%. In Europe, the prevalence of Salmonella spp.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…in live chickens at the time of slaughtering differs across countries. A recent study in Egypt ( Elsayed et al, 2024 ) revealed rates comparable to those in Jordan, with a range of 12 to 17%, while a study in Lebanon ( El Hage et al, 2022 ) revealed rates as high as 31.4%. In Europe, the prevalence of Salmonella spp.…”
Section: Discussionmentioning
confidence: 92%
“…In the European Union (Authority, 2017) , only 0.3% of Salmonella spp. were detected, whereas 31% were detected in Lebanon ( El Hage et al, 2022 ), 5% in Ecuador ( Vinueza-Burgos et al, 2019 ) and 11% in Brazil ( Herman et al, 2003 ). This low prevalence may be attributed to the sanitary and biosecurity conditions in the hatchery, which contribute to the low prevalence in parent stocks.…”
Section: Discussionmentioning
confidence: 99%
“…The antagonistic activity and co-aggregation ability of the lactobacilli strains were tested on three native avian Salmonella strains isolated from our previous study [ 4 , 49 ]. S .…”
Section: Methodsmentioning
confidence: 99%
“…In developing countries, a high prevalence of Salmonella has been recorded, ranging from 13% to 39% in South America, estimated at 35% in Africa, and ranging from 35% to 50% in Asia [ 3 ]. In Lebanon, according to our recent study, the percentage of contamination of poultry meat at the retail level (supermarkets and restaurants) was estimated at 22.4% [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Based on the White-Kauffmann-Le Minor method, over 2,650 distinct serotypes of Salmonella have been identified by their distinctive combinations of somatic (O) and flagellar (H) antigens (1,2). The infection of Salmonella enterica, like S. Enteritidis, S. Typhimurium, S. Infantis and S. Kentucky, in poultry and poultry products is on the rise (3,4). Fowls are the specific host of Salmonella enterica serovar Gallinarum biovars Pullorum and Gallinarum.…”
Section: Introductionmentioning
confidence: 99%